Catálogo de padrões de software no desenvolvimento de projetos acadêmicos em parceria com outras instituições - Silva, Caroline Guterres (2022)
Universities have established partnerships with companies and/or government aiming at the development of technological innovation projects to generate solutions based on problems presented by government institutions and companies. In this context, the “triple helix” model has been widely used for focusing on university-company-government relations as a means of encouraging the dynamics of innovation. Software development is one of the areas where these partnerships are commonly established. For these projects to be successful, it is necessary to define software processes that can deal with the characteristics of the institutions involved and the problem. Based on a systematic literature review, a lack of appropriate software processes for projects developed in academia was identified. This study aims to propose a catalog of patterns, documenting practices and techniques recommended in the literature and which have been adopted in the development of academic software processes involving external partnerships. The standards consider academic environments that develop projects in partnership with other institutions as a context for use. Patterns describe solutions to problems and challenges identified in the university environment in which software development will take place. After preparing the catalog, according to the problems identified in the university environment, development practices will be recommended to be used in the specific process for this project in partnership with other institutions. As a result of this study, a catalog of recommendations for software development practices suitable for academic projects carried out in partnership with companies and/or government was defined, according to the characteristics of the project. The validation through the questionnaire showed that most of the software standards presented can solve the identified problem, according to the positive feedback of the participants, based on the practical experience of software development. The proposed catalog can assist the software development team in making decisions regarding software practices, as well as being extended to other situational contexts.